“The money and children” in the book “Misers” by Al-Jahiz - Al-Abidi, Laila (Al-Adab Journal, 2022)
In Al-Bukhala by Al-Jahiz, the family plays an important role. It attracted our attention immediately, and we noticed that, despite its relevance, it did not receive an independent study on its own in all published research on the book in the Arabic, French and English languages. Therefore, we decided to devote to her this article, which we worked on, to monitor all the anecdotes, sayings and news related to the family, wife and children in Al-Jahiz’s book, then analyze and interpret them based on what modern knowledge provides us with in sociology, the psyche, anthropology, philosophy and other knowledge in order to reach a comprehensive scientific understanding of the miser’s behavior toward those closest to him, especially his wife and dependents, on the one hand, and his representations of them based on his (egotism) centrality, which is inextricably linked to the centrality of money "the pole on which the world revolves" in his social philosophy on the other. If money is the compass that leads him to everything including himself, then how about his wife and his dependents. We realized that this would not happen without it having repercussions on his psyche and behavior, diverting him from the norm and from the habit, and without reflecting on his relationship with the people closest to him. A complex relationship that we have worked to dismantle and uncover the dialectical dualities that organize it: love and hate - connection and separation - attraction and alienation - exclusion, integration and other dualities.